Local Mechanical Properties at the Dendrite Scale of Ni-Based Superalloys Studied by Advanced High Temperature Indentation Creep and Micropillar Compression Tests - Haußmann, Lukas; Neumeier, Steffen; Kolb, Markus; Ast, Johannes; Mohanty, Gaurav; Michler, Johann; Göken, Mathias (Minerals, Metals and Materials Series, 2020)
Chemical inhomogenities due to dendritic solidification of Ni-based superalloys result in different local microstructures with varying mechanical properties. New indentation creep test methods allow probing of the local creep properties at the dendrite scale at high temperatures. The as-cast single crystalline Ni-based superalloy ERBO1A (a derivative alloy of CMSX–4) was investigated and electron-probe microanalysis (EPMA) measurements revealed strong segregation of, e.g., Re and W in the dendritic region and, e.g., Ta in the interdendritic region. Indentation creep experiments at 750 °C and micropillar compression tests at 785 °C were conducted in both regions, and a higher creep strength was found in the dendritic region compared to the interdendritic region. Theoretical models for solid solution hardening as well as γ′ precipitation hardening confirm these results, since they predict a higher strength in the dendritic region than in the interdendritic region. Compared with the fully heat treated state, a smaller difference in the local mechanical properties or even a reverse strength ratio of the dendritic and interdendritic region can be expected.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dendritic segregations; Indentation creep; Micropillar compression; Ni-based superalloy